2020
DOI: 10.3390/pharmaceutics12030234
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability of Rifampicin in the Presence of Gastric-Resistant Isoniazid Microspheres in Acidic Media

Abstract: The degradation of rifampicin (RIF) in an acidic medium to form 3-formyl rifamycin SV, a poorly absorbed compound, is accelerated in the presence of isoniazid, contributing to the poor bioavailability of rifampicin. This manuscript presents a novel approach in which isoniazid is formulated into gastric-resistant sustained-release microspheres and RIF into microporous floating sustained-release microspheres to reduce the potential for interaction between RIF and isoniazid (INH) in an acidic environment. Hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The findings from this research design indicate that drug:polymer (X1) and surfactant (X2) greatly affected FLS-MS. For the quadratic models, the superlative fit for t 50 % (Y1), Q90 (Y2) and percentage drug content (Y3) was observed owing to its highest r 2 in contrast to linear, Two Factor Interaction (2-FI) and cubic models [25,30] (Table 2). Hence, the quadratic approach was developed to identify the effects of variables on response parameters as shown:Yi=b0+b1X1+b2X2+b12X1X2+b1 3B showed a significant linear curve running through the origin, which confirmed that response parameters were conjunctiva with predicted value [23,24] .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The findings from this research design indicate that drug:polymer (X1) and surfactant (X2) greatly affected FLS-MS. For the quadratic models, the superlative fit for t 50 % (Y1), Q90 (Y2) and percentage drug content (Y3) was observed owing to its highest r 2 in contrast to linear, Two Factor Interaction (2-FI) and cubic models [25,30] (Table 2). Hence, the quadratic approach was developed to identify the effects of variables on response parameters as shown:Yi=b0+b1X1+b2X2+b12X1X2+b1 3B showed a significant linear curve running through the origin, which confirmed that response parameters were conjunctiva with predicted value [23,24] .…”
Section: Resultsmentioning
confidence: 90%
“…Diagnostic plots were developed by Design-Expert software to investigate the goodness of fit of proposed model. Three-dimensional response surface graphs as well as corresponding two-dimensional contour graphs were developed using the Design-Expert software model graph tool to bestow graphical display of influence of independent variables on dependent parameters [23][24][25] .…”
Section: Statistical Diagnostic and Response Surface Analysis Of Experimental Data By Design-expert Softwarementioning
confidence: 99%
“…KSL-W is a synthetic antibacterial peptide, which can effectively kill oral bacterial pathogens and inhibit oral biofilm formation. And the microsphere system prepared by PLGA can not only have an obviously sustained and controlled release effect on drugs, but also protect bioactive materials from the degradation of the corresponding environment and improve bioavailability, which has great potential for medical application [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In general the inclusion of polymers, lipids, and surfactants for the production of suitable carriers for medicinal and non-medicinal applications has been demonstrated and opportunities to produce technologies that exhibit advantages over conventional formulations including improved stability, enhanced and beneficial biodistribution profiles, altered drug release rates, lower immunotoxicity and with potential targeting of specific cells, exists [ 108 ]. Micro- and/or nano-encapsulation has been used to develop sustained/prolonged drug delivery technologies [ 30 , 109 , 110 ], minimise degradation in biological fluids [ 111 ], facilitate handling [ 112 ] reduce toxicity [ 109 , 113 , 114 , 115 ] and to improve the organoleptic properties [ 19 , 116 , 117 ] of products.…”
Section: Encapsulation and Evaluation Of Therapeutic Benefits Of Curmentioning
confidence: 99%